Efficacy of rituximab (anti-CD20) for refractory systemic lupus erythematosus involving the central nervous system. Issue 4 (15th November 2006) - Tokunaga, Mikiko; Saito, Kazuyoshi; Kawabata, Daisuke; Imura, Yoshitaka; Fujii, Takao; Nakayamada, Shingo; Tsujimura, Shizuyo; Nawata, Masao; Iwata, Shigeru; Azuma, Taeko; Mimori, Tsuneyo; Tanaka, Yoshiya
Abstract : Aim: Neuropsychiatric systemic lupus erythematosus (NPSLE) is a serious treatment-resistant phenotype of systemic lupus erythematosus. A standard treatment for NPSLE is not available. This report describes the clinical and laboratory tests of 10 patients with NPSLE before and after rituximab treatment, including changes in lymphocyte phenotypes. Methods: Rituximab was administered at different doses in 10 patients with refractory NPSLE, despite intensive treatment. Results: Treatment with rituximab resulted in rapid improvement of central nervous system-related manifestations, particularly acute confusional state. Rituximab also improved cognitive dysfunction, psychosis and seizure, and reduced the SLE Disease Activity Index Score at day 28 in all 10 patients. These effects lasted for >1 year in five patients. Flow cytometric analysis showed that rituximab down regulated CD40 and CD80 on B cells and CD40L, CD69 and inducible costimulator on CD4+ T cells. Conclusions: Rituximab rapidly improved refractory NPSLE, as evident by resolution of various clinical signs and symptoms and improvement of radiographic findings. The down regulation of functional molecules on B and T cells suggests that rituximab modulates the interaction of activated B and T cells through costimulatory molecules. These results warrant further analysis of rituximab as treatment for NPSLE.